New cytotoxic limonoids from the stem bark of Chisocheton pentandrus (Blanco) Merr. (February 2020) - Supratman, Unang; Salam, Supriatno; Naibaho, Wiro; Fajar, Mohamad; Nurlelasari,; Katja, Dewa Gede; Harneti, Desi; Maharani, Rani; Hidayat, Ace Tatang; Lesmana, Ronny; Azlan Nafiah, Mohamad; Shiono, Yoshihito
Graphical abstract: Highlights: Three new limonoids, pentandricine B–D (1 –3 ), were isolated from Chisocheton pentandrus along with four known limonoids (4 -7 ). The structures were elucidated based on NMR and HR-TOFMS spectral data. Isolated compounds, 1 -7, were tested for their cytotoxic effects against MCF-7 breast cancer cells in vitro. Nimonol (7 ) showed strongest activity with an IC50 value of 22.03 ± 0.026 μM. Abstract: Three new limonoids namely pentandricines B–D (1–3 ), were isolated from n -hexane extract of the stem bark of Chisocheton pentandrus, along with four known limonoids (4-7) . The chemical structures of pentandricines B–D, were fully elucidated based on UV, IR, HR-TOFMS, 1D- and 2D-NMR spectra. Furthermore, compounds 1 -7 were evaluated for their cytotoxic activity against MCF-7 breast cancer cells in vitro, with compound 7 (nimonol) showing strongest cytotoxicity activity with an IC50 value of 22.03 ± 0.026 μM.